PLANTS USED TO COMBAT THE COVID-19 PANDEMIC IN AN INDIGENOUS URARINA COMMUNITY IN THE DEPARTMENT OF LORETO, PERU - DEL-AGUILA-VILLACORTA, Margarita (2021)
We report the plants used to combat the COVID-19 pandemic in a community of the Urarina indigenous people, in Loreto, Peru. Semi-structured interviews were conducted with health promoters, wise men, leaders and teachers of the community during the first and second waves of the pandemic, from May 2020 to June 2021. It was not possible to make trips to the community during the first wave of infections, so the interviews were carried out by telephone or through messaging applications such as WhatsApp or Messenger. During the second wave, field work was carried out, complementing the information with direct interviews with community residents and focus groups about the use of the plants. The plants used were collected from the places identified in the interviews and in the different focus groups. 16 plant species used specifically in the pandemic were identified. Four of them were introduced in America from the 16th century and are commonly used in an integrated way with species that are traditionally used in the community. Four species were also identified that have been used to strengthen the body and spirit against the COVID-19 disease.